Evaluation of bone involvement in patients with Gaucher disease: a semi‐quantitative magnetic resonance imaging method (using ROI estimation of bone lesion) as an alternative method to semi‐quantitative methods used so far. (23rd March 2015) - Komninaka, Veroniki; Kolomodi, Dionysia; Christoulas, Dimitrios; Marinakis, Theodoros; Papatheodorou, Athanasios; Repa, Konstantina; Voskaridou, Ersi; Revenas, Konstantinos; Terpos, Evangelos
Abstract Objective The aim of this study was to evaluate bone involvement in patients with Gaucher disease (GD) and to propose a novel semi‐quantitative magnetic resonance imaging (MRI) staging. Methods MRI of the lumbar spine, femur, and tibia was performed in 24 patients with GD and 24 healthy controls. We also measured circulating levels of C‐C motif ligand‐3 (CCL‐3) chemokine, C‐telopeptide of collagen type‐1 (CTX), and tartrate‐resistant acid phosphatase isoform type‐b (TRACP‐5b). Results We used the following staging based on MRI data: stage I: region of interest (ROI) 1/2 of normal values and bone infiltration up to 30%; stage II: ROI 1/3 of normal values and bone infiltration from 30 to 60%; stage III: ROI 1/4 of normal values and bone infiltration from 60% to 80%; and stage IV: detection of epiphyseal infiltration, osteonecrosis and deformity regardless of the ROI's values. All but two patients had abnormal MRI findings: 9 (37.5%), 6 (25%), 3 (12.5%), and 4 (16.7%) had stages I–IV, respectively. Patients with GD had elevated chitotriosidase, serum TRACP‐5b, and CCL‐3 levels (P < 0.001). Conclusions We propose an easily reproducible semi‐quantitative scoring system and confirm that patients with GD have abnormal MRI bone findings and enhanced osteoclast activity possibly due to elevated CCL‐3.